Respons Siswa Terhadap Aplikasi "BANG SIKUNG" Berbasis Android - Nursyam, Febriyani; Widyawati, Eka; Mucti, Alfian (Mathematics Education And Application Journal (META), 2022)
Android-based media is one of the newest types of media that utilizes technology in learning. To find out whether the media used is good or not in learning, student responses are needed. Therefore, this study was intended to determine student responses to the "BANG SIKUNG" application. The type of research is descriptive research with a quantitative approach. Student responses came from a sample of 15 students from class IX-7 with a sampling technique using purposive sampling. The instrument used is a questionnaire that has been validated by previous researchers with a total of 17 statements. The analysis was carried out using data categorization techniques. The results showed that the average student response was 92.25 in the "Very Good" category. Thus, the "BANG SIKUNG" application received a positive response from students.Keywords: Learning Media, Student Response, BANG SIKUNGMedia berbasis android merupakan salah satu jenis media terbaru yang memanfaatkan teknologi dalam pembelajaran. Untuk mengetahui media yang digunakan baik atau tidak dalam pembelajaran, diperlukan respon siswa. Oleh sebab itu, penelitian ini dimaksudkan untuk mengetahui respon siswa terhadap aplikasi â€œBANG SIKUNGâ€. Jenis penelitian yaitu penelitian deskriptif dengan pendekatan kuantitatif. Respon siswa berasal dari sampel sebanyak 15 siswa dari kelas IX-7 dengan teknik sampling menggunakan purposive sampling. Instrumen yang digunakan berupa angket yang telah divaliditas oleh peneliti sebelumnya dengan jumlah pernyataan sebanyak 17 butir. Analisis dilakukan dengan menggunakan Teknik kategorisasi data. Hasil penelitian menunjukkan rata-rata respon siswa sebesar 92.25 degan kategori â€œSangat Baikâ€. Dengan demikian, apliaksi â€œBANG SIKUNGâ€ memperoleh respon positif dari siswa.Kata kunci: Media Pembelajaran, Respon Siswa, BANG SIKUNG